Development of electrochemical-thermal modelling for large-format Li-ion battery. (1st July 2020) - Hou, Min; Hu, Yiyang; Zhang, Jianbang; Cao, Hui; Wang, Zhenbo
Abstract: Considering the non-homogeneous microstructure due to materials and fabrication process of large-format lithium-ion batteries, an effective electrochemical-thermal model is necessary for modern Li-ion battery (LIB) industry. In this work we developed a simplified model by using parallel method to study large-format Li-ion batteries. In particular, an approach in a combination of Maxwell-Cattaneo-Vernotte theory and Marcus-Hush-Chidsey kinetics was developed to determine the effect of lithium ion transport inertia and electron transfer behavior within 3D electrodes. To clearly verify the effectiveness of the developed model, temperature distribution measurements of a 155 Ah prismatic-type Li-ion batteries were carried out by using four built-in temperature sensors during charge and discharge process at different current densities. The simulation error of the studied model is only within 1.7 °C at 1.0C discharge, for 2.0C discharge, the error is 3.9 °C, which provide very strong verifications. We found that the hottest zone inside the battery is around the positive connector. The simulation studies also found that the internal currents of large-format batteries are unstable during constant current discharge process. During a discharge process at 2.0C, local internal current in some areas even reached 6.0C and negative current is also detected as well. This means that the local redox direction can be significantly changed in a large-format LIB. This phenomenon can be explained by the nonuniform distribution of reactant concentration and temperature inside the studied batteries. This work introduced an effective approach to establish a model for LIB industry, which can be used as a fast and accurate diagnosis method to design optimal parameters for large-format LIB batteries. Graphical abstract: Image 1 Highlights: A simplified electrochemical-thermal model is proposed for large-format lithium-ion batteries. A 155 Ah prismatic-type LIB is used to validate our model. The local nonuniformities within a large-format cell caused by both fabrication and raw materials are fully considered in the model. The distribution of internal current in a large-format Lithium-ion battery is studied.